Pengaruh Penambahan Limbah Plastik Jenis Thermosetting Terhadap Parameter Marshall Laston AC-WC - Kusdiyono Kusdiyono; Supriyadi Supriyadi; Tedjo Mulyono; Sukoyo Sukoyo (Politeknik Negeri Semarang, 2019)
At present, plastic is a material that is needed by the community at large, where the impact is also very extraordinary after the plastic is used in everyday life which can cause serious problems if the management is not done properly. The problem of plastic waste does not only occur in the city of Semarang, but also in other cities, so that the Ministry of Environment and Forestry has implemented a paid plastic bag program in the short term. But this is only to deal with problems in the short term. In the long run, it will not solve the problem of